Impact of Ivermectin Mass Drug Administration for Lymphatic Filariasis on Scabies in Eight Villages in Kongwa District, Tanzania - Martin, Diana (Am J Trop Med Hyg, 2018)
Scabies was recently added to the World Health Organization list of neglected tropical diseases. The ability to treat scabies with oral ivermectin makes a mass drug administration (MDA) campaign a feasible option for scabies control. Ivermectin MDA in communities endemic for lymphatic filariasis (LF) or onchocerciasis may already be having an impact on scabies. We examined the effect of ivermectin MDA for LF on scabies prevalence over 4 years in eight Tanzanian villages. At baseline, 4.4% (95% confidence interval [CI]: 3.7–5.4) of individuals tested positive for scabies, decreasing to 0.84% (95% CI: 0.51–1.4) after one round of ivermectin MDA but increased in Year 3 (2.5% [95% CI: 1.9–3.3]) and Year 4 (2.9% [95% CI: 2.2–3.8]). Most scabies cases were seen in children younger than 15 years. The data suggest that single-dose ivermectin MDA may not be effective in attaining long-term decreases when scabies prevalence is less than 5%.